Catalog of the Diptera types described by Camillo Rondani - Sforzi, Alessandra; Sommaggio, Daniele (Zootaxa, 2021)
This catalog lists all 1226 nominal species introduced by Rondani within Diptera (1174 available and 52 unavailable), providing for each available name data on the type locality, type material, current taxonomic status and with remarks on both the collectors and the specialists who have studied this material. The following new synonymies are proposed: Panops aeneus Philippi, 1865 [Acroceridae] under Lasia aenea Rondani, 1863, n. syn.; Panops nigripes Philippi, 1865 [Acroceridae] under Lasia cuprea Rondani, 1863, n. syn.; Tabanus brasiliensis Rondani, 1850 [Tabanidae] under Dichelacera fasciata Walker, 1850, n. syn.; Petagnia subpetiolata Rondani, 1859 [Tachinidae] under Petagnia occlusa Rondani, 1856, n. syn.; Tephritis siderata Rondani, 1868 [Tephritidae] under Hexacinia radiosa (Rondani, 1868), n. syn. Mallophora macquartii Rondani 1851 [Asilidae] is considered as a senior (but invalid) synonym of Mallophora scopipeda Rondani, 1863, n. syn. Paragus mundus Wollaston, 1858 [Syrphidae] is proposed as the valid name for Paragus coadunatus sensu Goeldlin de Tiefenau (1976); Paragus coadunatus Rondani, 1847 [Syrphidae] is reinstated as a junior synonym of Paragus haemorrhous Meigen 1822. Lectotypes are designated herein for the following nominal species: Domomyza anthracipes Rondani, 1875, Domomyza frontella Rondani, 1875 [both in Agromyzidae]; Chorthophila impudica Rondani, 1866 [Anthomyiidae]; Sephanilla sertulata Rondani, 1875 [Aulacigastridae]; Peratochetus lutescens Rondani, 1856 [Clusiidae]; Myopa punctum Rondani, 1857 [Conopidae]; Culex pulcritarsis Rondani, 1872 [Culicidae]; Ephydra ciligena Rondani, 1868 [Ephydridae]; Lonchea scutellaris Rondani, 1875 [Lonchaeidae]; Geomyza pictipennis Rondani, 1875 [Opomyzidae]; Megaglossa vegetationis Rondani, 1869 [Platystomatidae]; Eumerus tuberculatus Rondani, 1857, Merodon varius Rondani, 1845, Paragus mundus Wollaston, 1858, Pipizella neuphritica Rondani, 1868 [all in Syrphidae]; Exorista noctuicida Rondani, 1859, Phoricheta lacrimans Rondani, 1861 [both in Tachinidae]; Tephritis decipiens Rondani, 1871, Tephritis matutina Rondani, 1871, Urophora lejura Rondani, 1870, Urophora venabulata Rondani, 1870, Urophora veruata Rondani, 1870 [all in Tephritidae]. The following nominal species have lectotypes designated according to Article 74.5 of the I.C.Z.N. Code: Chortophila divergens Rondani, 1866, Chortophila incognita Rondani, 1866 [both in Anthomyiidae]; Habropogon doriae Rondani, 1873, Promacus taeniopus Rondani, 1873 [both in Asilidae]; Chelidomyia melbae Rondani, 1879, Myophthiria lygaeoides Rondani, 1878, Ornithomya gestroi Rondani, 1878, Ornithomya hatamensis Rondani, 1878 [all in Hippoboscidae]; Megaglossa corticarum Rondani, 1869 [Platystomatidae]; Elgiva lateritia Rondani, 1868, Tetanocera nigricosta Rondani, 1868, Tetanocera punctifrons Rondani, 1868 [all in Sciomyzidae]; Tabanus justorius Rondani, 1875 [Tabanidae]. The following lectotypes are designated by inference according to Article 74.6 of I.C.Z.N.: Diopsis aethiopica Rondani, 1873, Diopsis latimana Rondani, 1875, Teleopsis breviscopium Rondani, 1875, Teleopsis longiscopium Rondani, 1875 [all in Diopsidae]; Cyclopodia albertisii Rondani, 1878, Myophthiria reduvioides Rondani, 1875 [both in Hippoboscidae]; Myiodella brachialis Rondani, 1873, Senopterina zonalis Rondani, 1875 [all in Platystomatidae]; Stevenia florentina Rondani, 1861 [Rhinophoridae]; Miltogramma punctatella Rondani, 1868 [Sarcophagidae]; Sargus leoninus Rondani, 1875 [Stratiomyidae]; Chrysops alter Rondani, 1875, Chrysops unizonatus Rondani, 1875, Tabanus dives Rondani, 1875, Tabanus fulvissimus Rondani, 1875, Tabanus ignobilis Rondani, 1875 [all in Tabanidae]; Themara hirtipes Rondani, 1875 [Tephritidae]. The following names are new combinations: Diopsis latimana Rondani, 1875 [Diopsidae] is transferred to Teleopsis and kept as a junior synonym of Teleopsis dalmanni (Wiedemann, 1830), comb. nov.; Diopsis lativola Rondani, 1875 [Diopsidae] is transferred to Teleopsis and kept as a junior synonym of Teleopsis dalmanni (Wiedemann, 1830), comb. nov. The following names, previously deemed unavailable, are determined here to be available: Petagnia occlusa Rondani, 1856 [Tachinidae]; Tephritis siderata Rondani, 1868 [Tephritidae]. The following names, previous deemed available, are determined here to be unavailable: Porricondyla albitarsis Rondani, 1840 [Cecidomyiidae], Lucilia cyanicolor Rondani, 1850 [Calliphoridae]; Cephenemya stimulatrix Rondani, 1857 [Oestridae]; Cheilosia nigricornis Rondani, 1844, Cheilosia testacicornis Rondani, 1857, Pelecocera ruficornis Rondani, 1865 [all in Syrphidae]; Cylindrogaster sanguinea Rondani, 1861, Deximorpha cristata Rondani, 1862, Myostoma microcera Rondani, 1856 [all in Tachinidae]; Tripeta exacheta Rondani, 1870 [Tephritidae]. We consider Merodon italicus Rondani 1845 as an unnecessary substitute name for Merodon natans Fabricius, 1794 and confirm it as a junior synonym of Merodon natans Fabricius, 1794. Acting as First Revisers, the following are herein selected as correct original spellings: Trichophthalma philippii Rondani, 1863 [Nemestrinidae]; Sphiximorpha garibaldii Rondani, 1860 [Syrphidae]; Agelanius philippii Rondani, 1863 [Tabanidae]; Exorista achanthina Rondani, 1859, Platychyra brevicauda Rondani, 1865 [Tachinidae]. Species not previously treated in any recent Diptera catalog include the following: Chorthophila limbatella Rondani, 1877, Hylephila melitensis Rondani 1877 [both in Anthomyiidae]; Mya jonicroma Rondani, 1851, Mya versicolor Rondani, 1850, Somomya anulipes Rondani, 1863, Somomyia xanthomera Rondani, 1875 [all in Calliphoridae]; Madiza fabae Rondani, 1876 [Chloropidae]; Psilopus ducalis Rondani, 1850 [Dolichopodidae]; Gymnopa opaca Rondani, 1869 [Ephydridae]; Oedalea bracata Rondani, 1856 [Hybotidae]; Sapromyza albifrons Rondani, 1868, Sapromyza rectinervis Rondani, 1868 [both in Lauxaniidae]; Boletina parmensis Rondani, 1856, Bolithobia lateralis Rondani, 1856, Bolithomyza spinulina Rondani, 1856, Mycetomyza sciarina Rondani, 1856, Pachipalpus calceatus Rondani, 1856 [all in Mycetophilidae]; Lyoneura lugubris Rondani, 1856 [Psychodidae]; Volucella trizonata Rondani, 1875 [Syrphidae]; Echinomya apicalis Rondani, 1848, Echinomya ignobilis Rondani, 1863, Gonia ornata var. repudiata Rondani, 1859, Hyalomyia unicolor Rondani, 1868, Platychyra valida Rondani, 1865, Pyragrura uncinatus Rondani, 1861 [all in Tachinidae]. One species, Bertea subaptera Rondani, 1856, is returned to Diptera from Hymenoptera after examination of the type material.